Економічна ризикостійкість як основа механізму управління інноваційним розвитком підприємства - Клюс, Ю.І.; Водяник, Р.В. (Економічний вісник Донбасу, 2022)
В статті доведено, що створення механізму забезпечення стійкості при реалізації інноваційних стратегій, на думку авторів, має бути засноване на використанні такої системної характеристики підприємства як ризикостійкість. Дано визначення стійкому інноваційному розвитку, проведено порівняльний аналіз категорій «економічний ризик» та «економічна ризикостійкість». Запропоновано розгляд поняття ризикостійкості як системної характеристики підприємства в контексті взаємозв'язків категорій ризик, стійкість та розвиток. Визначено роль економічної ризикостійкості у системі управління розвитком виробничого підприємства. Доведено, що категорія «економічний ризик» нерозривно пов'язана з цілями підприємства, зв'язуючи цілі діяльності та використані для досягнення цих цілей економічні ресурси (втрати ресурсів) різного виду та фактичні результати. The article proves that the creation of a mechanism for ensuring stability in the implementation of innovative strategies, according to the authors, should be based on the use of such a systemic characteristic of the enterprise as risk resistance, which depends on special disturbing influences caused by a high level of environmental instability and the specificity of cyclical innovation processes; in the context of enterprise or situation management, it characterizes the ability of the management apparatus to adequately respond to the threats of risk factors in view of internal vulnerabilities, using reserved resources for the purpose of normal business operations; creates for the enterprise conditions for purposeful functioning and implementation of innovative projects under the conditions of emergency situations. The definition of sustainable innovative development was given, a comparative analysis of the categories "economic risk" and "economic risk resistance" was carried out. The dual role of risk resistance in the enterprise management system consists in the fact that, on the one hand, risk resistance creates conditions for purposeful functioning and development, affects integral performance results, and on the other hand, it is determined by the complex of interactions of the enterprise with higher-level systems, internal and external factors that can become risk factors in conditions of an economic crisis and an unstable environment. It is proposed to consider the concept of risk tolerance as a system characteristic of the enterprise in the context of interrelationships between the categories of risk, sustainability and development. The role of economic risk tolerance in the system of managing the development of a manufacturing enterprise is determined. It is proved that the category "economic risk" is inextricably linked with the goals of the enterprise, linking the goals of activity and the economic resources used to achieve these goals (resource losses) of various types and actual results. It was determined that the development of the innovative development management mechanism is related to the determination of the parameters of the controlled system and the standardization of their levels. Of course, the main controlled parameter can be the level of risk tolerance, which indirectly characterizes the value of system negentropy. Therefore, the sustainability of the enterprise during the implementation of innovative strategies is related to maintaining the level of risk tolerance. Its value in relation to certain types of resources and potential components is the basis of managing the economic situation, as it affects the choice of managerial influences.